2020
DOI: 10.18043/ncm.81.5.315
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Self-compassion, and Mental Health Outcomes

Abstract: Natural disasters have occurred more frequently in Eastern North Carolina in recent years. Evidence supports that repeated exposure to natural disasters may have lasting mental health impacts among vulnerable populations. Greater access to mental health services may aid in ensuring equitable access to needed care and promote resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…This finding is similar to the results of other studies that have shown that other pre-COVID-19 factors, specifically coping and emotion regulation, predicted mental health during the pandemic (Tyra et al, 2021). The findings of this study suggest that mindful self-compassion training can support better mental health in individuals living in high-risk contexts (Van der Gucht et al, 2015) and during community-level disasters or stressors (e.g., Lea et al, 2020). In sum, although mindful self-compassion was not related to appraisal and coping, it was related directly to mental health, thus suggesting that there are other possible mechanisms accounting for their effects.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is similar to the results of other studies that have shown that other pre-COVID-19 factors, specifically coping and emotion regulation, predicted mental health during the pandemic (Tyra et al, 2021). The findings of this study suggest that mindful self-compassion training can support better mental health in individuals living in high-risk contexts (Van der Gucht et al, 2015) and during community-level disasters or stressors (e.g., Lea et al, 2020). In sum, although mindful self-compassion was not related to appraisal and coping, it was related directly to mental health, thus suggesting that there are other possible mechanisms accounting for their effects.…”
Section: Discussionsupporting
confidence: 90%
“…Despite ca. $3.5 billion of state and federal funding spent on recovery efforts from Hurricanes Matthew (2016) and Florence (2018) [17], there was a lack of preparedness (e.g., lack of updated maps, communication issues) of many eastern NC counties after Hurricane Florence. This lead to the development of a statewide mosquito control services contract (duration of current contract: August…”
Section: Introductionmentioning
confidence: 99%
“…Receiving instrumental support might also encourage growth in other ways as well. It may directly change how an individual interacts with strangers in their community, it may result in spiritual change through experiences with meaningful connection, and it may inspire a new outlook on the future as others step in to help individuals with matters they could not manage on their own (Lea et al, 2020; Tedeschi & Moore, 2021).…”
mentioning
confidence: 99%
“…The SSDM highlights that people do not all have equal access to support or do not equally use support and that these differences can influence postdisaster adaptation outcomes (Guilaran et al, 2018; Hobfoll et al, 2007). Coping strategy use and receipt of instrumental support generally peaks in the initial weeks following a disaster (Lea et al, 2020), but as months pass, previously accessible support often becomes less available (Norris & Kaniasty, 1996). For many, the continuing need for instrumental support is likely to outstrip available support.…”
mentioning
confidence: 99%